Pengembangan Agrowisata di Desa Tenganan Dauh Tukad, Kecamatan Manggis, Kabupaten Karangasem - WIDANA, I MADE KUSUMA; BUDIASA, I WAYAN; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Development of Agrowisata in Tenganan Dauh Tukad Village, Manggis District, Karangasem District Tenganan Dauh Tukad Village is one of the villages located close to popular tourist sites in Karangasem Regency. Tenganan Dauh Tukad Village is considered to have the potential to develop agro-tourism. A study study that discusses these potentials and strategies is needed so that this research is carried out. This research aims to see the potential in Tenganan Dauh Tukad Village, Manggis District, Karangasem Regency and to develop agro-tourism development strategies in Tenganan Dauh Tukad Village, Manggis District, Karangasem Regency The data methods are observation, in-depth interviews, and literature study. The research data were analyzed using descriptive qualitative methods. The results showed that the village of Tenganan Dauh Tukad has a potential attraction that can be developed as agro-tourism. The development strategy that can be carried out in Tenganan Dauh Tukad Village is a Stability Strategy that is implemented without changing the direction of the strategy that has been set.